Inter-relationships of depression and anxiety symptoms among widowed and non-widowed older adults: findings from the Chinese Longitudinal Healthy Longevity Survey based on network analysis and propensity score matching - Li, Yinglin; Lin, Doudou; Gong, Xuan; Fu, Dou; Zhao, Ling; Chen, Weibing; Chen, Jie; Liu, Shanshan; Yang, Guirong; Cai, Zhongxiang (Frontiers in Public Health, 2025)
BackgroundDepression and anxiety are prevalent mental health issues among older adult widowed adults. However, the symptom-level relationships between these conditions remain unclear. Due to the high correlations and complex relationships among various symptoms, this study employs network analysis to explore differences in the network structures of depression and anxiety symptoms between widowed and non-widowed older adults.MethodsPropensity score matching was used to identify widowed older adults with similar demographic characteristics. Data from 1,736 widowed and 1,736 matched controls were analyzed using the Chinese Longitudinal Healthy Longevity Survey (2017–2018). Depression and anxiety were measured by the Center for Epidemiologic Studies Depression Scale-10 (CESD-10) and the seven-item Generalized Anxiety Disorder Scale (GAD-7), respectively. Central and bridge symptoms were evaluated using expected influence (EI) and bridge expected influence (BEI), respectively.ResultsNetwork analysis revealed similarities in central symptoms between widowed and non-widowed older adults, with both groups exhibiting “Feeling depressed or down” (CESD3), “Feeling tense and having difficulty relaxing” (GAD4), and “Being unable to stop or control worrying” (GAD2) as core symptoms. However, differences emerged in bridge symptoms. In the widowed group, “Feeling anxious, worried, or distressed” (GAD1) was most strongly connected to “Felt lonely” (CESD8); “Worrying too much about various things” (GAD3) was strongly linked to “Feeling increasingly exhausted and useless with age” (CESD4); and “Feeling depressed or down” (CESD3) had a strong association with “Becoming easily annoyed or irritable” (GAD6). In the non-widowed group, “Feeling anxious, worried, or distressed” (GAD1) exhibited the strongest association with “Having good sleep quality” (CESD10); “Getting upset over small matters” (CESD1) was closely connected to “Feeling anxious, worried, or distressed” (GAD1); and “Worrying too much about various things” (GAD3) was most strongly connected to “Feeling depressed or down” (CESD3).ConclusionCommon central and bridge symptoms highlight universal intervention targets. Addressing “Feeling depressed or down” in widowed and “Getting upset over small matters” in non-widowed older adults may help prevent depression-anxiety comorbidity. These findings support targeted interventions to improve mental health outcomes. Future research should evaluate tailored intervention effectiveness.